A comparative study of streptococcal antigen-binding human T8+ cells and monocytes, in relation to the HLA-DRw6 locus and the helper, suppressor and contrasuppressor functions. - Lehner, T (1984)
Binding of streptococcal antigen was compared between T8+ cells and monocytes (Mo) from DRw6+ and DRw6- subjects. Both T8+ cells and Mo from DRw6- subjects bind streptococcal antigen (SA) specifically and almost entirely at a concentration of 1000 ng per 0.1 ml. However, the DRw6+, T8+ cells bind SA at a concentration of 1 ng but the DRw6+ Mo bind SA at both 1 and 1000 ng of SA per 0.1 ml. The HLA-DR-dependent shift in the binding concentration of SA applied to Mo as well as T8+ cells, except that the DRw6+ Mo showed a biphasic response (1 and 1000 ng) of SA binding. Comparative inhibition studies revealed that the antigen binding T8+ cells, unlike Mo, are inhibited with monoclonal anti-T8 and -T5 antibodies and anti-suppressor factor antiserum. Neither cell was inhibited by anti- T4, M1, F(ab), IgG, IgM, VH null cell or helper factor antibodies, and anti-T3 antibodies showed variable inhibition of SA binding to T8+ cells but no inhibition to Mo. A functional comparison was carried out between the antigen binding cells and helper and suppressor activities in unseparated mononuclear cells. T4-depleted and T8-depleted populations of cells. The concentration of SA binding to the T8+ cells was the same as that required to elicit helper activity but reciprocal to the broad range of SA concentrations necessary to induce suppressor cell activity. The results are interpreted on the basis of the hypothesis that the antigen binding T8+ cell functions as a contrasuppressor cell which prevents the major subset of the T8+ cells inhibiting the T4+ cells.